2022
DOI: 10.1039/d2sc01899c
|View full text |Cite
|
Sign up to set email alerts
|

Accessing the triplet state of perylenediimide by radical-enhanced intersystem crossing

Abstract: Owing to their exceptional photophysical properties and high photostability, perylene diimide (PDI) chromophores have found various applications as building blocks of materials for organic electronics. In many light-induced processes in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 87 publications
2
33
0
3
Order By: Relevance
“…In this series, perylene is covalently bound to seven different radicals, which are commonly used in experimental studies on molecular three-spin systems. [45][46][47][48][49][50][51][52][53][54] The goal was to determine the influence of the nature of the radical on the magnitude of the exchange interaction(s) and to verify whether systematic trends can be identified. Fig.…”
Section: Choice Of the Molecules And Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this series, perylene is covalently bound to seven different radicals, which are commonly used in experimental studies on molecular three-spin systems. [45][46][47][48][49][50][51][52][53][54] The goal was to determine the influence of the nature of the radical on the magnitude of the exchange interaction(s) and to verify whether systematic trends can be identified. Fig.…”
Section: Choice Of the Molecules And Methodsmentioning
confidence: 99%
“…In this series, perylene is covalently bound to seven different radicals, which are commonly used in experimental studies on molecular three-spin systems. 45–54…”
Section: Theorymentioning
confidence: 99%
“…Management of the spin state in spintronic materials can be useful to affect display efficiency of organic light-emitting diodes, among other applications. , For example, an aromatic compound such as benzene and pyridine can be directly excited to the triplet state in the presence of a free radical species such as oxygen and NO, , whereas the triplet state of closed-shell porphyrins can become highly luminescent with an unpaired metal d-electron . In a recent biomolecular application of the spintronic coupling between 9,10-anthraquinone and a stable nitroxide radical (Figure A), it was found that its spin state can be controlled by visible light through DNA binding.…”
Section: Illustrative Examplesmentioning
confidence: 99%
“…Management of spin state in spintronic materials can be useful to affect display efficiency of organic light-emitting diode, among other applications. 63,64 For example, an aromatic compound such as benzene and pyridine can be directly excited to the triplet state in the presence of a free radical species such as oxygen and NO, 65,66 whereas the triplet state of closed-shell porphyrins can become highly luminescent with an unpaired metal d-electron. 67 In a recent biomolecular application of the spintronic coupling between 9,10anthraquinone and a stable nitroxide radical (Figure 2A), 68 it was found that its spin state can be controlled by visible light through DNA binding.…”
Section: Spin Coupling Of Anthraquinone and Nitroxide Free Radicalmentioning
confidence: 99%